2018
DOI: 10.5812/jjcdc.68310
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Medication Adherence Among Iranian Elderly Patients with Chronic Diseases

Abstract: Background: One of the most important problems of the elderly with chronic diseases is lack of medication adherence that imposes huge costs on every country health care system. Objectives: The aim of present study was to examine effective determinants on medication adherence in elderly patients with chronic diseases. Methods: A cross-sectional survey was conducted at two teaching hospitals in Qom, Iran, in 2016. A total of 100 patients aged 60 and older were selected by convenience sampling. Data collection to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In relation to age group, the result of this study projected that non-adherence to glaucoma medications among the elderly participants have represented a 2013) reported that the rates of non-adherence to medication is high among older adults over the age of 60 years compared to any other age groups and increased gradually with advanced age where the glaucoma prevalence increases dramatically with age which may result in intensely the elderly population with glaucoma-related visual disability. (18,19,49,52,53) In addition, Al-Mansouri, Kanaan, Gamra, Khandekar, Hashim Al Qahtani, & Ahmed,(2011) revealed that glaucoma and different visual disabilities among subjected aged 40-49 years were not available as the visual acuity for the blindness and low vision study focused on the subjects 50 years or older. In other words, subjects among the age group of 60 years and older had a significantly higher risk of glaucoma compared with subjects in the 40-59 years age group (P =0.00001).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to age group, the result of this study projected that non-adherence to glaucoma medications among the elderly participants have represented a 2013) reported that the rates of non-adherence to medication is high among older adults over the age of 60 years compared to any other age groups and increased gradually with advanced age where the glaucoma prevalence increases dramatically with age which may result in intensely the elderly population with glaucoma-related visual disability. (18,19,49,52,53) In addition, Al-Mansouri, Kanaan, Gamra, Khandekar, Hashim Al Qahtani, & Ahmed,(2011) revealed that glaucoma and different visual disabilities among subjected aged 40-49 years were not available as the visual acuity for the blindness and low vision study focused on the subjects 50 years or older. In other words, subjects among the age group of 60 years and older had a significantly higher risk of glaucoma compared with subjects in the 40-59 years age group (P =0.00001).…”
Section: Discussionmentioning
confidence: 99%
“…G*power (version 3.1.2) software (franz faul, universitat Kiel, Germany) was used to determine the sample size. based on a previous report [17], the minimum sample size was estimated to be 318 people, for two-tailed tests, α = 0.05, 95% confidence level, a possibility of 10% loss and an expected frequency of patient errors of 71%.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…There is little information about the rate of adherence with the treatment regimen in HF patients in Iran. In one study [11], 60.3% of patients and in another study [12], 71.4% of patients had poor self-reported medication adherence. Adherence to treatment in HF is a multidimensional phenomenon influenced by the interplay of several factors, such as socioeconomic factors (age, gender, race, and lack of access to transportation), health care system-related factors (inadequate education of health care providers in chronic diseases, shortened time of visits by the physician, and lack of insurance support), patient-related factors (forgetfulness, improvement or reduction of symptoms, and knowledge deficiency), condition-related factors (severity of illness and depression), and therapy-related factors (side effects and the number of medications taken during the day) [9,[13][14][15].…”
Section: Introductionmentioning
confidence: 96%